Adapting Brief Behavioral Treatment for Insomnia for Former National Football League Players: A Pilot Study. Issue 3 (4th May 2023) - Wanberg, Lindsey J.; Thomas, S. Justin; Reid, Michelle; Rottapel, Rebecca; von Ash, Tayla; Jones, Nicole; Brar, Laurie; Beidas, Rinad; Rueschman, Michael; Edwards, Robert R.; Buysse, Daniel J.; Redline, Susan; et al.
ABSTRACT: Objectives: Insomnia is highly prevalent among persons with chronic pain. Although cognitive behavioral therapy for insomnia is recommended as first-line treatment for insomnia, it is underutilized. We tested the feasibility of a potentially scalable alternative – Brief Behavioral Therapy for Insomnia (BBTI) for former National Football League (NFL) players, a group with a high prevalence of chronic pain. We assessed changes in sleep, pain, and psychological health. Methods: Single-arm clinical trial of an adapted telephone-delivered BBTI intervention in 40 former NFL players with insomnia. We collected data on changes in sleep, pain, and psychological health outcomes. Results: Among former players (30% racial/ethnic minorities), BBTI was both acceptable and feasible. BBTI was associated with improvements in sleep disturbance (primary exploratory sleep outcome, mean T-score change −6.2, 95% CI: −7.6, −4.8), sleep-related impairment (mean T-score change −5.7, 95% CI: −7.9, −3.5) and insomnia severity (mean change −5.3, 95% CI: −6.8, −3.5) post-intervention. Improvements were maintained at 2-months. BBTI was also associated with improvements in pain interference and intensity, but not psychological health. Conclusion: An adapted telephone-delivered BBTI is acceptable and feasible among retired players with a range of insomnia symptoms and shows promise for improving sleep and pain. These data support the need for future trials assessing BBTI's effect on both sleep and pain outcomes.